ASSESSMENT OF VALUABLE DOMESTIC VARIETIES OF GRAIN CROPS NOWADAYS - V. I. Makarov (Зерновое хозяйство России, 2018)
The analysis of average month temperatures in Tula region shows that during last 20 years the summer time lasts 19 days more, the autumn time last 11 days more in average. In 1995-2014 the average temperature in a vegetation period exceeded the same figures in 1945-1974 on 1,68˚С. The autumn of the previous 20-year period (August, September, October) is characterized by heavy precipitations, but there is a deficit of moisture in June and July. Thus the researches of a comparative assessment of productivity of southern grain crops grown in the Middle part under various climatic conditions are of great importance.  The article gives the results of a comparative assessment of productivity winter and spring wheat and winter triticale varieties of southern selection grown in the Middle part during the years with various climatic conditions. The assessment of the varieties on maximum and minimum productivity shows that the varieties ‘Smuglyanka’, ‘Favoritka’, ‘Biryuza’ are characterized by better figures under different agro climatic conditions. The study of spring wheat selected in Krasnodar RIA showed that the productivity of the crops varied from 2,37 to 4,18 t/ha in average. The most productive variety was the variety ‘Kurier’ in average during six years. Winter triticale produced 6-8,5 t/ha with a minimum fertilizers and without pesticides. The greatest average productivity along five years of researches was given by the varieties ‘Bard’, ‘Tribun’, ‘Nina’, ‘Nemchinovskaya 56’ and ‘Vasilisa’. Thus, making estimation of the varieties of southern selection and marking their highest potential we can conclude on a necessity to expand and improve interregional connection of grain crops.